Shift of indirect to direct bandgap and thermoelectric response of the cubic BiScO3 via DFT-mBJ studies. (July 2016) - Noor, N.A.; Rashid, Muhammad; Alay-e-Abbas, S.M.; Raza, Mohsin; Mahmood, Asif; Ramay, Shahid M.; Murtaza, G.
Abstract: The mechanical, electronic, optical and thermoelectric properties of cubic perovskite BiScO3 are studied by using density functional theory. The lattice parameter of BiScO3 calculated at zero pressure indicates good agreement with similar compounds crystallizing in the cubic perovskite structure. The exchange-correlation functional based on Perdew-Burke-Ernzerhof GGA has been used for calculating structural and mechanical properties, while the functional proposed by Tran and Blaha in the form of modified Becke-Johnson (mBJ) exchange potential has been employed to calculate the electronic, optical and thermoelectric properties. The elastic constants and bulk modulus are calculated and their pressure dependence upto 50 GPa has been investigated. Cubic BiScO3 is found to be an indirect bandgap semiconductor at ambient pressure, while a direct bandgap appears under the influence of pressure. In addition to the electronic properties, the dielectric function, refractive index, reflectivity, extinction coefficient and absorption spectrum are also presented. Moreover, important thermoelectric properties of the compounds are explained in terms of electrical conductivity, thermal conductivity, Seebeck coefficient and figure of merit.